The Effect of Job Satisfaction, Discipline, and Work Environment on Employee Work Improvement at the Serdang Bedagai Regency DPRD Office - Nurul Fachira; Slamet Widodo (Penerbit Jurnal Indonesia, 2025)
The Effect of Job Satisfaction, Discipline, and Work Environment on Employee Work Improvement at the Serdang Bedagai Regency DPRD Office. Under the guidance of Slamet Widodo. This study aims to analyze the influence of job satisfaction, discipline, and work environment on the improvement of employee work at the Serdang Bedagai Regency DPRD Office. Using a quantitative method with a survey approach, data was obtained through a questionnaire distributed to 30 respondents. The results of multiple linear regression analysis show that the three independent variables have a significant influence on employee performance. This study provides recommendations to improve job satisfaction, discipline, and the quality of the work environment to increase employee productivity. A neat and comfortable work environment can be ensured to make employee performance achieve in accordance with the vision and mission of the Secretariat of the Regional House of Representatives of Serdang Bedagai Regency. In this study, quantitative data and qualitative data research are used. There are two sources of data used, namely primary data and secondary data. The research method uses the explanatory survey method. This study was conducted on 30 employees by distributing preliminary questionnaires and follow-up questionnaires on variables X and Y. The research used the Nonprobability Sampling method. The coefficient hypothesis test uses the SPSS program.